Concentrações séricas de progesterona e colesterol em cabras mestiças alimentadas com dietas hiperlipídicas no início da gestação - Velásquez, Luis Fernando Uribe [UNESP] (1996)
The effects of hyperlipidic diets on the blood serum concentration of progesterone and cholesterol in the early pregnancy of 32 crossbred goats were studied. The goats were allocated to four treatments: 1) restricted intake; 2) full feed(control); 3 and 4) hiperlipidic diets with 2.5 and 5.0 % tallow, respectively. The goats submitted to a restricted intake showed lower concentrations of blood serum progesterone and cholesterol at 9,15,18, and 21 days of pregnancy. The intake of hyperlipidic diets had a quadratic effect on blood serum progesterone concentrations. Goats treated with 2.5 % ,tallow showed higher blood serum progesterone concentrations at 15, 18, and 21 days of pregnancy. It was concluded that goats treated with hyperlipidic diets had higher concentrations of blood serum cholesterol at the beginning of pregnancy. The DM and NDF intakes by the goats were different among diets with a lower intake by goats fed the hyperlipidic diet with 5.0% tallow.